2009
DOI: 10.1186/1471-2121-10-63
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide (GX1) homing to gastric cancer vasculature inhibits angiogenesis and cooperates with TNF alpha in anti-tumor therapy

Abstract: Background: The discovery of the importance of angiogenesis in tumor growth has emphasized the need to find specific vascular targets for tumor-targeted therapies. Previously, using phage display technology, we identified the peptide GX1 as having the ability to target the gastric cancer vasculature. The present study investigated the bioactivities of GX1, as well as its potential ability to cooperate with recombinant mutant human tumor necrosis factor alpha (rmhTNFα), in gastric cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Endostar treatment slightly reduced the cell number, and the cell viability of HUVECs was 74.75%±4.27% (P,0.05). In contrast, GPEN treatment more effectively reduced HUVEC viability [34][35][36] These data indicated that GPENs showed a better antitumor cell effect than free Endostar in vitro and therefore possessed potential applications in antitumor treatment in vivo.…”
Section: The Effects Of Gpens On Cell Viability In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Endostar treatment slightly reduced the cell number, and the cell viability of HUVECs was 74.75%±4.27% (P,0.05). In contrast, GPEN treatment more effectively reduced HUVEC viability [34][35][36] These data indicated that GPENs showed a better antitumor cell effect than free Endostar in vitro and therefore possessed potential applications in antitumor treatment in vivo.…”
Section: The Effects Of Gpens On Cell Viability In Vitromentioning
confidence: 99%
“…12,13 The GX1 peptide (CGNSNPKSC), identified by phage-display technology, has been demonstrated as a tumor vasculature endothelium-specific ligand. [14][15][16] Previous studies pointed out that the GX1 peptide plays a role in gastric cancer-associated angiogenesis, suggesting that GX1 peptide-based assays may be one method to image tumor angiogenesis to improve diagnosis and therapy.…”
mentioning
confidence: 99%
“…The present study revels mutation of TNF-α gene (either complete deletion/ over expression / under expression) may failed to contributes the significant development of the tissue architecture required necessary for tumor growth & metastasis [18]. These tumor-promoting activities suggest that inhibition of TNF-α is an effective strategy for cancer therapy [21] thus TNF-α gene mutation are involved in the complications during pregnancy and extend their effects to increase "risk factor" for development of cancer.…”
Section: Discussionmentioning
confidence: 62%
“…Tumor necrosis factor (TNF), act as an anti-tumor cytokine is an another candidate gene with multifunctional activity in inflammation, immunity, cellular homeostasis and tumor progression [16] through NK cells, T cells, B cells and macrophages mediated killing of specific tumors (soft tissue sarcoma, melanoma) [17], gastric tumors [18]. TNF-α is able to initiate cellular apoptosis and deactivate tumor cells in solid cancer and to maintain microenvironment promotes cell migration and invasion [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the RGD and GX1 peptides play an active role in targeting the tumor. A large number of literatures reported that RGD and GX1 peptides could specifically target to α v β 3 -integrin 2,49,50 and vasculature endothelium receptors, [51][52][53][54] respectively, which were excessively expressed on plasma membrane of tumor cells. In addition, the distribution mode of double ligand-modified NPs was significantly different from those of the free DOX and single ligand-modified NPs.…”
Section: Distribution Resultsmentioning
confidence: 99%